PERSEPSI PORNOGRAFI ANTARA KONTROVERSI DAN KEBEBASAN BEREKSPRESI (Studi Fenomenologi Tentang Pengalaman Kognitif Anggota fansclub “Lady Gaga Indo” Terkait Persepsi Pornografi Antara Kontroversi dan Kebebasan Berekspresi Pada Diri Lady Gaga) - Nur Desilawati; Fitri Lestari Permata Hati; Imelia Pebreyanti; Willy Willy (Universitas Bunda Mulia, 2013)
Pornography is a controversial topic, especially in Indonesia. There’s always ‘pro’ and ‘contra’ opinion. Some people who are pro to pornography see that it as a part of freedom of expression; meanwhile some consider that pornography doesn’t fit to religion’s values. Furthermore, pornography is an impact from foreign culture’s intervention through internet, film, song until artist like Lady Gaga. This figure is considered as a symbol of pornography because of her controversial performance. Briefly, her tour to Indonesia had been cancelled.Keywords: pornography, fans, phenomenology, cognitive